1996
DOI: 10.1042/bj3150127
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Zn2+-binding site in human serum butyrylcholinesterase

Abstract: Purified human serum butyrylcholinesterase after treatment with either of the metal chelators EDTA or NaCN was able to bind to a Zn(2+)-chelate-Sepharose affinity column and was eluted from the column by EDTA or imidazole. Prior EDTA treatment of the enzyme was essential for binding to this affinity column. The enzyme could be labelled with (65)Zn(2+) after EDTA treatment of the enzyme. Diethylpyrocarbonate modification of histidine residues in the EDTA-treated enzyme resulted in the abolition of both binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…Although the mechanism by which ChEs are inhibited by heavy metals is unclear, our results sustain the hypothesis that metal cations inactivate AChE and BChE (Masson et al 1996, Guilhermino et al 1998. Cd 2+ is known to inhibit BChE from human serum (Sarkarati et al 1999) and sheep brain (Çoku-ras & Tezcan 1993) and it has been suggested that human serum BChE has more than one binding motif for divalent cations (Bhanumathy & Balasubramanian 1996.…”
Section: Aquatic Pollutantssupporting
confidence: 86%
“…Although the mechanism by which ChEs are inhibited by heavy metals is unclear, our results sustain the hypothesis that metal cations inactivate AChE and BChE (Masson et al 1996, Guilhermino et al 1998. Cd 2+ is known to inhibit BChE from human serum (Sarkarati et al 1999) and sheep brain (Çoku-ras & Tezcan 1993) and it has been suggested that human serum BChE has more than one binding motif for divalent cations (Bhanumathy & Balasubramanian 1996.…”
Section: Aquatic Pollutantssupporting
confidence: 86%
“…Comparison of the effects of monovalent and divalent ions on the activity of AChE suggests a general screening effect of monovalent cations, while it has been proposed that divalent cations interact specifically with carboxylate groups present in the active site (Hofer et al, 1984). The identification of a putative binding site for Zn 2+ in hBChE (Bhanumathy and Balasubramanian, 1996) supports the notion of specific binding sites for divalent cations in ChEs.…”
Section: Module Ii: the Potential Gradient Along The Active-site Gorgsupporting
confidence: 57%
“…Comparison of the effects of monovalent and divalent ions on the activity of AChE suggests a general screening effect of monovalent cations, while it has been proposed that divalent cations interact specifically with carboxylate groups present in the active site (Hofer et al, 1984). The identification of a putative binding site for Zn 2ϩ in hBChE (Bhanumathy and Balasubramanian, 1996) supports the notion of specific binding sites for divalent cations in ChEs.…”
Section: Module Ii: the Potential Gradient Along The Active-site Gorge Is Responsible For Steering Cationic Species To The Active Site Ofmentioning
confidence: 71%